2001
DOI: 10.1038/ncb0901-844
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint activation in response to double-strand breaks requires the Mre11/Rad50/Xrs2 complex

Abstract: Studies of human Nijmegen breakage syndrome (NBS) cells have led to the proposal that the Mre11/Rad50/ NBS1 complex, which is involved in the repair of DNA double-strand breaks (DSBs), might also function in activating the DNA damage checkpoint pathways after DSBs occur. We have studied the role of the homologous budding yeast complex, Mre11/Rad50/Xrs2, in checkpoint activation in response to DSB-inducing agents. Here we show that this complex is required for phosphorylation and activation of the Rad53 and Chk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
132
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 28 publications
11
132
0
Order By: Relevance
“…Analysis of ATM activation and substrates such as SMC1 showed that the ATM signalling cascade was activated in these treatments and was affected by tungstate [3]. The MRN complex has diverse functions in DNA damage recognition [34], cell cycle checkpoint activation [35], non-homologous end joining [36] and telomere maintenance [37]. The MRN complex binds DSB soon after they are formed implicating it in DNA damage detection [38], thus acting upstream ATM and allowing its activation.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of ATM activation and substrates such as SMC1 showed that the ATM signalling cascade was activated in these treatments and was affected by tungstate [3]. The MRN complex has diverse functions in DNA damage recognition [34], cell cycle checkpoint activation [35], non-homologous end joining [36] and telomere maintenance [37]. The MRN complex binds DSB soon after they are formed implicating it in DNA damage detection [38], thus acting upstream ATM and allowing its activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ATLD cells display normal activation of the ATM/CHK2/CDC25A pathway after exposure to ionizing radiation (Falck et al, 2002), suggesting that hMre11 may be involved only in the ATM/NBS1/ SMC1 pathway for intra-S phase checkpoint control, as observed in NBS cells. In contrast to the observation in vertebrates, yeast Mre11-mutant cells display defects in phosphorylation of yRad53 (the yeast homolog of CHK2) after treatment with bleomycin and hydroxyurea and hence, yeast intra-S phase checkpoint could be regulated by Mec1/yRad53 (ATR/CHK2 homologs) pathway (Grenon et al, 2001;D'Amours and Jackson, 2001).…”
Section: Nbs1 In Cell-cycle Checkpoint Controlmentioning
confidence: 99%
“…14). Without resection, mre11Δ G2-arrested cells also fail to activate the DNA damage checkpoint 15 (Fig. 3c).…”
mentioning
confidence: 99%
“…Because Mre11 is required for DSB resection and checkpoint activation 1,15,16 , we asked whether defective resection caused by CDK1 inactivation reflects the inability to load Mre11 on broken chromosomes. We found Mre11 at DSBs in G2 cells ( Fig.…”
mentioning
confidence: 99%